Understanding paediatric data standards challenges through academia‐industry partnerships: A conect4children (c4c) qualitative study. (5th November 2022) - Sen, Anando; Palmeri, Avril; Lee, Joanne; Hedley, Victoria; Thuet, Jacques; Lignon, Perrine; Cotonnec, Valerie; Leary, Rebecca; Nally, Sinéad; Straub, Volker
Abstract: Introduction: The conect4children (c4c) consortium was setup to facilitate the development of new drugs and therapies for paediatric populations and address key challenges associated with paediatric clinical trials. Two of the major adopting principles for c4c were academia‐industry partnership and data harmonisation and interoperability through common eCRF definitions. To understand the challenges arising out of these principles, the c4c team at Newcastle University conducted semi‐structured interviews with four c4c industry partners. Methods: Each partner was asked 10 questions about the data standards used in their company, management and maintenance of data dictionaries, how they dealt with paediatric‐specific issues, major knowledge gaps and how academia could aid in bridging these gaps. Thematic analysis was performed to identify patterns in their answers. Results: All companies use the Clinical Data Interchange Standards Consortium (CDISC) standards but face problems when certain terminology is not included in CDISC (e.g., paediatric‐specific terminologies). All companies were committed to interoperability and had strict policies about how additional terminology could be added to their dictionaries. Three of the four companies maintained a single dictionary but also had lighter versions for specific usage. The two major knowledge gaps identified from the interviews were handling of non‐CDISC terminology and maintenance of normal lab ranges in dictionaries. Discussion: To address these gaps, c4c has been working on a four‐point plan including the development of a cross‐cutting paediatric dictionary and a paediatric user guide in collaboration with CDISC. Key points: Academia‐industry collaborations are crucial for paediatric clinical trials. Pharmaceutical companies committed to interoperability. Non‐CDISC data items challenge interoperability between and within companies. c4c is developing resources to aid interoperability through collaborations.